Robotic-Assisted Surgery for Cadaveric Skull Opening: A New Method of Autopsy Procedure - Jumlongkul, Arnon; Chutivongse, Panuwat (Frontiers in Robotics and AI, 2021)
Background: Sawing of bone is an essential part of an autopsy procedure. An oscillating saw always generates noise, fine infectious dust particles, and the possibility of traumatic injuries, all of which can induce occupational hazard risks to autopsy workers, especially in COVID-19 pandemic. Objectives: The first goal of this study was to explore the production of noise and bone dust emission, comparing an oscillating saw and a robotic autopsy saw during an autopsy. The second goal was to evaluate the performance of a new robotic autopsy method, used during skull opening. The third goal was to encourage mortuary workers to use robotic technology during the autopsy procedure to protect us away from occupational injuries as well as airborne infections. Materials and methods: The experiments involved a comparison of noise levels and aerosol production during skull cutting between the oscillating saw and the robotic autopsy saw. Results: The results confirmed that noise production from the robotic autopsy saw was lower than the oscillating saw. However, the bone dust levels, produced by the robotic autopsy saw, were greater than the oscillating saw, but were not greater than the dust concentrations which were present before opening the skull. Conclusions: The use of a new robotic system might be an alternative choice for protecting against occupational damage among the healthcare workers. Further research might attempt to consider other healthcare problems which occur in the autopsy workplace and apply the robotic-assisted technology in autopsy surgery.